Drosha, DGCR8, and Dicer mRNAs are downregulated in human cells infected with dengue virus 4 (2016)
ABSTRACT: Dear Editor, A recent paper (Casseb et al., 2016) published in the journal Genetics and Molecular Research described the interesting concept that dengue virus (DENV)-4 infection, in the human cell line A-549, leads to the downregulation of expression of key components of microRNA (miRNA) biogenesis, such as Drosha, Dicer, and DGCR8. For this, the authors performed a time course infection of A-549 cells for 5 days. The highest viral load was observed at 3 days post-infection, which corresponded with the maximum downregulation of expression of Drosha, Dicer, and DGCR8, assayed by quantitative PCR (RT-qPCR). These results supported the recent notion of a complex interaction between DENV and the host miRNA machinery and of the host miRNA response to this particular infection. Extensive evidence has shown that DENV can take advantage of host miRNAs for its own replication (Zhu et al., 2014) and that host miRNAs can inhibit DENV replication (Wu et al., 2013).